Dynamics of Financial Development and Foreign Direct Investment on Nepal’s Economic Growth: A NARDL Analysis - Adhikari, Padma Kumar; Pandey, Abhishek; Shrestha, Zenisha (Economic Review of Nepal, 2023)
This study explores the asymmetric effects of financial development and foreign direct investment (FDI) on economic growth in Nepal, employing the nonlinear autoregressive distributed lag (NARDL) model. The analysis reveals significant asymmetries in the effects of FDI and financial broadening in the economy by distinguishing between positive and negative shocks, the outcome indicates that positive shocks in financial sector growth significantly boost the economy, while negative shocks have a less pronounced and statistically insignificant effect. Similarly, positive shocks in FDI positively influence GDP per capita growth, whereas negative shocks are statistically insignificant. The robustness of these findings shows stable model parameters. The study underscores the importance of proactive policy measures to harness the positive impacts of financial development and FDI, thereby fostering sustained economic growth in Nepal. These insights contribute to the broader literature by highlighting the need for asymmetric analysis in understanding the complex dynamics of financial development, FDI, and economic growth in developing economies.